Pengaruh Experiential Marketing, Service Innovation, Brand Image terhadap Customer Satisfaction dan Customer Loyalty - Angelia, Jeveline; Nisa, Puspita Chairun (Jurnal Nasional Manajemen Pemasaran dan SDM, 2025)
Customers often rely on reviews because customer satisfaction can create value for companies and is an important element in attracting new customers in a more efficient way than retaining existing customers. This study aims to analyse the influence of experiential marketing, service innovation, and brand image on customer satisfaction, as well as the influence of customer satisfaction on customer loyalty. Data collection was conducted among customers of Janji Jiwa coffee shops in the Jakarta and Bekasi areas, aged 17 years or older and with a minimum of two purchases within three months. This study employs a quantitative approach using descriptive causality methods and Structural Equation Modelling – Partial Least Squares (SEM-PLS) analysis techniques. The sample size consists of 125 respondents selected using purposive sampling. The results of the study indicate that experiential marketing, service innovation, and brand image each have a positive and significant influence on customer satisfaction. Furthermore, customer satisfaction was also found to have a positive and significant influence on customer loyalty. The managerial implications of this study suggest that Janji Jiwa should strengthen customer experience, develop experiential marketing and service innovation, and maintain brand image to ensure that customer satisfaction and customer loyalty continue to increase sustainably.